(untitled) (Journal of actual problems of jurisprudence, 2024)
The protection of children’s rights and their safety is one of the priorities of the State’s social policy. This year, President Kassym-Jomart Kemelovich signed a law on the payment of funds to children from the National Fund. On January 1, 2024, the National Fund for Children project will be launched in Kazakhstan. While the bright future of Kazakhstan is in the hands of a generation that is not indifferent to the fate of the country, truly patriotic, purposeful, interested, the formation of a high-quality human capital is in the hands of the authorities. The state constantly supports the future of children and adolescents, their high–quality education, health promotion and the formation of family and moral and spiritual values - the key to a bright future for our country. The Head of State demands urgent resolution of issues related to the rights of the child, the immediate entry into force of laws related to the rights of the child. In his speech, the President noted that «we must solve large-scale issues of protecting the rights of the child. We must strengthen state control and consider effective mechanisms to ensure the safety of children, prevent suicide and bullying among children» (https://egemen.kz/article/261356-qasym-zhomart-toqaev-balalar-arasyndaghy-suitsid-pen-bullingtinh-aldyn-alu-qadge.). The year 2022 has been declared the year of children, the rights of the child are widely promoted, measures for their rights have been implemented in each region of the republic, and a lot of work has been done. Key words: the Commissioner for the Rights of the Child, the rights and duties of the child, orphans, social orphans, the Commissioner for Human Rights, the family.